Trellis-Coded Quantization of Phases in MISO Wireless Systems - Jianfeng Zhang; Dongjian He; Yong Fang; Lvwen Huang (Institute of Advanced Engineering and Science, 2012)
This correspondence considers multiple-input single-output (MISO) wireless systems with equal gain transmission (EGT) at the transmitter and maximum ratio combining (MRC) at the receiver. In such systems, the receiver feedbacks the elemental phases of beam-forming vectors to the transmitter. Due to finite feedback rate, the elemental phases of beam-forming vectors have to be quantized effectively before feedback. This correspondence makes use of the trellis-coded quantization (TCQ) to quantize elemental phases of beam-forming vectors. The principle of TCQ and its application to phase quantization are introduced in detail. Representative simulation results are given to verify the superiority of TCQ phase quantization over other quantization schemes. The research results can be applied to the image information such as wireless transmission systems on many agricultural robots to work together, improve the efficiency and reliability of information transmission. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1579